IMPLIKASI PENAMBANGAN PASIR DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT PADAIDI KAB. PINRANG - Muhammad Akbar; Zainal Said; Rusnaena (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
School cooperatives are cooperatives whose members are students or students of a school that serves as a forum for educating the growing awareness of cooperatives among students. For this reason, we need a forum that is expected to be able to achieve these objectives, namely school cooperatives. Cooperatives have a direct contribution to the welfare of their members because cooperatives have the principle of kinship and also the function of cooperatives for the welfare of their members. DDI Lilbanat Islamic boarding school as one of the business units, Islamic boarding schools aim to meet the needs of teachers and students in daily life. This research was conducted by raising the issue of: 1. How the efforts of DDI Lilbanat boarding school cooperatives in meeting the needs and improving the welfare of teachers and students, 2. How is the function of the DDI Lilbanat boarding school cooperatives in order to improve the welfare of teachers and students.This type of research used in this thesis is a qualitative descriptive method, the data in this study were obtained from primary data and secondary data. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used is the inductive method and the deductive method.Environmental problems will arise from the interaction between human economic activities and natural resources, which starts from the demand of the population for goods and services, which in turn results in increased demand for natural resources. Through economic activities, the natural resources are exploited to produce a product in the form of goods and services.In the kelurahan area in the exploitation of natural resources produced to produce goods or services carried out through sand mining, sand miners are one of the main economic growth factors in an area, especially in the sand mining location.This type of research used in this thesis is a qualitative descriptive method, the data in this study were obtained from primary data and secondary data. Data collection techniques used were interviews, observation, and documentation. The data analysis technique is to use qualitative data analysis.Implications in determining the results of research using a process that results in economic improvement by looking at the good and bad impacts and how to know the economic development of the community before and after the existence of a sand mine in Padaidi Village as a research location, and want to know how to analyze Islamic economic law.The results of this study indicate that: 1) the economic development of the community has been able to improve the economy of the community by looking at the economic development of the community before and after the existence of sand mining 2) the implications generated in seeing the positive and negative impacts have really helped the community, such as the opening of jobs and income levels for the community, and does not have too bad an impact on the environment